Formes frustes of Marfan's syndrome presenting with severe aortic regurgitation. Clinicogenetic study of 18 families. Issue 2 (February 1977) - Emanuel, R; Ng, R A; Marcomichelakis, J; Moores, E C; Jefferson, K E; MacFaul, P A; Withers, R
Abstract : Eighteen patients who presented with severe aortic regurgitation and dilatation of the ascending aorta were found to be formes frustes of Marfan's syndrome and formed the basis for this clinicogenetic study. All had aortic valve replacement and reconstruction of part of the ascending aorta. The diagnosis was confirmed by histological examination of the aortic tissue. There were 126 first degree relatives; 85 were living and 67 (78-8%) of these were examined. Limited information was available about 32 of the 41 relatives who had died. No relative had the classical clinical features of Marfan's syndrome but stigmata of the disease were found in 25 (37-3%) of the 67 first degree relatives examined. In 21, the abnormality was confined to the cardiovascular system, the skeleton, or the eye, but in 4, abnormalities involved 2 systems. Cardiovascular abnormalities affecting the aortic valve or aortic wall were present in 6 (9-0%) of the 67 first degree relatives examined. One or more of the skeletal indices measured (height-span difference, metacarpal index, phalangeal index) was abnormal in 18 (26-9%) and ocular abnormalities were found in 5 of 51 (9-8%) examined. There were no relatives with dislocation of the lens or iridodonesis. Using strict diagnostic criteria, a minimum of 37-3 per cent of the first degree relatives examined were affected; this involved 12 of the 18 families studied. There was nothing in our data to suggest that the formes frustes of the disease had a different mode of inheritance from the classical syndrome.